Comparative Evalution of Resin Based Sealer on Fracture Resistance of Endodontically Treated Teeth: An in Vitro Study (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Root canal therapy offers a chance to treat diseased or damaged teeth so they can continue to function normally in the dentition, but it also reduces the tooth's structural integrity, which lowers the teeth's resistance to fracture. Root canal sealers have recently been developed, and they are rumored to improve the bond strength between root canal filling materials and the root dentin, increasing the root's resistance to fracture. The aim of the study was to compare between AH Plus and MetaSEAL resin based root canalsealer on fracture resistance of endodontically treated teeth.Materials and methods: Thirty freshly extracted human mandibular premolar teeth were selected according to inclusion and exclusion criteria. All of them were decoronated up to cemento-enamel junction, and to have a 14 mm root length. Then teeth were divided into three groups (n=10). Group-1: AH Plus sealer, Group-2: MetaSEAL endodontic sealer and Group-3: neither instrumented nor obturated served as negative control. First two groups were instrumented using ProTaper rotary file (Dentsply, Sirona) system up to F3 fileas the final master apical file. Single cone obturationtechnique was carried out to both experimental groups. Fracture strength test was done by universal testing machine (Hounsfield, H1OKS,UK). The force required to fracture was recorded in Newton. The result was statistically analyzed using oneway analysis of varience (ANOVA) and post hoc test (Tukey’s HSD).Results: Group-1(AH Plus) showed higher fracture resistance force values than group 2 (MetaSEAL) significantly. There was insignificant difference between group 1 and 3.Conclusion: The use ofAH Plus sealer could produce more fracture resistance than MetaSEAL resin based sealer of endodontically treated teeth.JCMCTA 2022 ; 33 (2) : 120-125